1993
DOI: 10.1111/j.1475-1313.1993.tb00468.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of target luminance on microfluctuations of accommodation

Abstract: It is feasible that small temporal variations in steady-state accommodation may provide feedback to the accommodation control system through changes in retinal image contrast and that this feedback may be used to maintain an optimal accommodation response. The complex waveform of microfluctuations is dominated by two distinct regions of activity; a low frequency component (LFC < 0.6 Hz) and a high frequency component (1.0 < or = HFC < or = 2.3 Hz). Whereas the HFCs appear to be correlated with some intraocular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
87
0
2

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(93 citation statements)
references
References 32 publications
4
87
0
2
Order By: Relevance
“…These theories are supported by findings showing that the magnitude of the accommodation microfluctuations vary systematically with target characteristics such as target luminance (Day, Seidel, Gray, & Strang, 2009a;Gray, Winn, & Gilmartin, 1993b), the spatial frequency (SF) content of the stimulus (Niwa & Tokoro, 1998) as well as with variations in ocular depth of focus induced by alterations in pupil size (Campbell et al, 1959;Day et al, 2009a;Gray, Winn, & Gilmartin, 1993a;Stark & Atchison, 1997).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…These theories are supported by findings showing that the magnitude of the accommodation microfluctuations vary systematically with target characteristics such as target luminance (Day, Seidel, Gray, & Strang, 2009a;Gray, Winn, & Gilmartin, 1993b), the spatial frequency (SF) content of the stimulus (Niwa & Tokoro, 1998) as well as with variations in ocular depth of focus induced by alterations in pupil size (Campbell et al, 1959;Day et al, 2009a;Gray, Winn, & Gilmartin, 1993a;Stark & Atchison, 1997).…”
Section: Introductionmentioning
confidence: 81%
“…The shallower contrast gradient available at luminances e0.002 cd/m 2 is caused by a reduction in the SF content available to the accommodation error detector (Day et al, 2009a). Accommodation microfluctuations are found to increase in magnitude at these lower luminance levels, and it is thought that the microfluctuations increase because larger changes in focus are required to produce alterations in the contrast gradient detectable by the accommodation controller (Day et al, 2009a;Gray et al, 1993b).…”
Section: Introductionmentioning
confidence: 94%
“…The two groups reported contradictory results: According to Zeki, the illusion could be seen through the pinhole [and thus the percept was not caused by accommodation fluctuations (23)], whereas Gregory reported that the pinhole abolished the illusion (26). The logic underlying these experiments was problematic, however, because a pinhole does not optically mitigate accommodation fluctuations (51,53,54). Although a small pinhole will prevent large accommodative responses (such as those related to shifting one's gaze between objects located at different distances), it does not eliminate the accommodation fluctuations found during visual fixation.…”
Section: Debate On the Role Of Accommodation Fluctuations In Enigmamentioning
confidence: 90%
“…Zeki used both 1.6-and 2.2-mm pinholes (23), whereas Gregory used a 4-mm pinhole (26). Moreover, as pointed out by Mon-Williams and Wann (17), the 4-mm pinhole used by Gregory (26) was too big to prevent even large accommodative responses (51).…”
Section: Debate On the Role Of Accommodation Fluctuations In Enigmamentioning
confidence: 99%
See 1 more Smart Citation